KEPUASAN PELANGGAN TERHADAP LAYANAN PURNA JUAL ALAT BANTU OPERASIONAL PERBANKAN OLEH PT. MURNI SOLUSINDO NUSANTARA SURABAYA - Juita Alisjahbana (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
The aim of this research is to examine correlation of quality of after sales service and customer satisfaction at PT. Murni Solusindo Nusantara Surabaya. The survey method used in this research and data collecting technique are questionaires survey. The independent variable is service of quality with sub variables are  tangibles, reliability, responsiveness, assurance and empathy. The dependent variable is customer satisfaction. Dates were analized using multiple regression and correlation analysis. The result of this research shown that simultaneously  and partially tangibles, reliability, responsiveness, assurance and empathy have correlation  significant with customer satisfaction  with  regression  model is Y = 6,042 + 0,698 X1 + 0,788 X2 + 0,985 X3 + 0,70 X3 + 0,688 X5.